Emergence of Karachi as the Largest Industrial Region of Pakistan - Muhammad Jawed Iqbal; Ahsan Ullah (Journal of Basic & Applied Sciences, 2017)
The analysis based on the data published by the CMI (2005-06) remarkably brings out the outstanding position of Karachi as the largest industrial center of the country. Though the industrial development is spreading fast in other districts, Karachi continues to expand as the largest manufacturing region with unabated prospects and potential for further growth in the near future, since new areas in Karachi Division are being developed for export-oriented industry and hi-tech manufacturing. The high value addition in Karachi is a distinctive trend. McCarty’s measure of excess value added has been employed to ascertain the rank of Karachi as an apex industrial district in Pakistan.